A novel efficient route for removing Pb2+ ions from wastewater using 2-(4-nitrobenzylidene)malononitrile doped on Reed stems - Shahoo Ahmadi; Ghasem Marandi (Scientific Reports)
Abstract In this study, reed stalks enhanced with 2-(4-nitrobenzylidene)malononitrile were utilized to adsorb Pb2+ ions from wastewater. The primary advantage of this method, reported for the first time, is the flotation of the adsorbent by the reed stalk fibers after use. This process enables the adsorbent to be collected using strainer paper. The main action Pb2+ ions adsorption is facilitated by the cyanide groups in the adsorbent, which are present in the 2-(4-nitrobenzylidene)malononitrile compound. The synthesis of the adsorbent is carried out through a Novenagel reaction using malononitrile and 4-nitrobenzaldehyde. Furthermore, this study evaluates the impact of various conditions, including temperature, pH, and solution stirring speed, on adsorption efficiency. The most favorable outcomes were observed at a neutral pH. The decrease in vibrational absorption frequency in the cyanide groups following the absorption of Pb2+ ions indicate their role in removing lead ions. For the adsorption model calculations, three isotherm models- Langmuir, Freundlich, and Tamkin- were used. The results obtained from the experimental method are most consistent with the Temkin isotherm model. Additionally, the adsorption rate calculations of lead ions showed that they are most consistent with the zero-order rate. The results of this method are deemed satisfactory as a cost-effective alternative when compared to other more expensive procedures.